Sociodemographic Relationships with Self-Care Management Adherence in Type 2 Diabetes Mellitus Patients - Pitora, Tobi; azahra, Sahara; khoirunissa, kenssa; suryani, sri; sabrina, najwa; utami, winda (Poltekkes Kemenkes Banjarmasin, 2025)
Type 2 diabetes mellitus (T2DM) is a chronic disease with a high complication rate that is strongly influenced by patient compliance with self-care management. This study aims to analyze the forms of compliance that affect self-care management in T2DM, sociodemographic characteristics that play a role in self-care management, and aspects of self-care management that contribute to improving compliance of T2DM patients. The method used was literature from the EBSCO, SAGE, and PubMed databases for the period 2021-2025, with the inclusion criteria of English articles, full text, and the use of Medical Subject Headings (MeSH Terms). The literature review showed that adherence in the aspects of blood sugar monitoring, diet management, physical activity, medication consumption, and foot care determine the success of self-care management. Sociodemographic factors such as advanced age, low education and economic level, and lack of social support were shown to reduce patient adherence to self-care management. In contrast, patients with good health education, access to adequate medical equipment, and family and community support showed a more optimal level of compliance and self-care management. Effective self-care management, especially in terms of diet management, physical activity, and blood sugar monitoring, significantly increases patient compliance, reduces the risk of complications, and improves quality of life. Thus, sociodemographic-based interventions, health education, and family/community involvement are essential to improve adherence and effectiveness of self-care management in T2DM patients.